Alterations of white matter integrity related to motor activity in schizophrenia - Sebastian Walther; Andrea Federspiel; Helge Horn; Nadja Razavi; Roland Wiest; Thomas Dierks; Werner Strik; Thomas J. Müller (Neurobiology of Disease, 2011)
Altered structural connectivity is a key finding in schizophrenia, but the meaning of white matter alterations for behavior is rarely studied. In healthy subjects, motor activity correlated with white matter integrity in motor tracts. To explore the relation of motor activity and fractional anisotropy (FA) in schizophrenia, we investigated 19 schizophrenia patients and 24 healthy control subjects using Diffusion Tensor Imaging (DTI) and actigraphy on the same day. Schizophrenia patients had lower activity levels (AL). In both groups linear relations of AL and FA were detected in several brain regions. Schizophrenia patients had lower FA values in prefrontal and left temporal clusters. Furthermore, using a general linear model, we found linear negative associations of FA and AL underneath the right supplemental motor area (SMA), the right precentral gyrus and posterior cingulum in patients. This effect within the SMA was not seen in controls. This association in schizophrenia patients may contribute to the well known dysfunctions of motor control. Thus, structural disconnectivity could lead to disturbed motor behavior in schizophrenia.